2022
DOI: 10.1002/ece3.9532
|View full text |Cite|
|
Sign up to set email alerts
|

Divergent responses of butterflies and bees to burning and grazing management in tallgrass prairies

Abstract: Butterflies and bees contribute significantly to grassland biodiversity and play important roles as pollinators and herbivores. Grassland conservation and management must be seen through the lens of insect conservation and management if these species are to thrive. In North America, grasslands are a product of climate and natural disturbances such as fire and grazing. These natural disturbances have changed considerably since European colonization and subsequent landscape fragmentation. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…While Buckles and Harmon‐Threatt (2019) found a negative association between grazing and bee nesting, the two sites in our study with a history of grazing had the highest numbers of active nests in both burned and unburned areas. Thus, more work is needed to document whether prescribed burning confers fitness benefits to the ground‐nesting bee community and how other management techniques like grazing or haying may influence nest site choices (Leone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Buckles and Harmon‐Threatt (2019) found a negative association between grazing and bee nesting, the two sites in our study with a history of grazing had the highest numbers of active nests in both burned and unburned areas. Thus, more work is needed to document whether prescribed burning confers fitness benefits to the ground‐nesting bee community and how other management techniques like grazing or haying may influence nest site choices (Leone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies across a diversity of ecosystems have found positive effects of prescribed fire on bee abundance and diversity (Brown et al, 2017; Carbone et al, 2019; Mason et al, 2021; Smith DiCarlo et al, 2019; Ulyshen et al, 2021; Williams et al, 2010, but see Griffin et al, 2021 and Leone et al, 2022). The underlying mechanisms for bees' positive responses to fire are generally considered to be altered flowering phenology and floral density, with fire leading to higher floral densities (Mola & Williams, 2018; Ponisio, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Data for the wheatgrass sites can be found at Larson et al (2018) and Larson and Larson (2023) and for the tallgrass sites at Leone et al (2022a) Summaries of the data used in the analyses can be found in Tables A1 and A2. Code used for the analyses is in Supporting Information.…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…Both bowl traps and hand netting are often used in either inventory (Meiners et al., 2019 ) or hypothesis‐driven research (Lasway et al., 2022 ; Leone et al., 2022b ; Watson et al., 2011 ) because each method will capture somewhat different species. Common species have been found to be equally well represented by both methods, but rarer or more specialized species may be best captured by only one of the methods (Grundel, Frohnapple, et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, although many studies have examined the effects of fire on butterfly communities in other grassy biomes such as North American prairie (e.g., Leone et al, 2022; Moranz et al, 2012; Swengel, 1996; Vogel et al, 2010), only one published study has examined the effects of fire on butterfly communities in tropical savanna: in an African mesic savanna, Gaget et al (2020) found that butterfly abundance and species composition varied with fire frequency. However, the mechanisms behind these responses were not identified.…”
Section: Introductionmentioning
confidence: 99%